VisualGrid: enabling runtime applications monitoring in grid environments. (1st September 2010) - Minutoli, Giuseppe; Paone, Maurizio; Fazio, Maria; Puliafito, Antonio
Scientific visualisation represents an important tool to help researchers in understanding huge and complex results produced in the research laboratories. The purpose of this article is to describe how scientific visualisation techniques can be used in a grid environment in order to allow users to monitor the evolution of their applications. The development of an innovative software infrastructure, called 'VisualGrid', is described highlighting as the use of such solution may be very useful, especially in the presence of applications characterised by a long term execution. Users can save time by detecting misbehaviours or inefficiencies in their systems before the job execution on the grid infrastructure is finished. Technical and practical problems encountered during the development of 'VisualGrid' are discussed and a performance evaluation of the developed prototype is presented.